2015
DOI: 10.1158/0008-5472.can-14-3098
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Induces Programmed Cell Death-Ligand 1 Overexpression via the Nuclear Factor-κB to Foster an Immunosuppressive Tumor Microenvironment in Ovarian Cancer

Abstract: Emerging evidence has highlighted the host immune system in modulating the patient response to chemotherapy, but the mechanism of this modulation remains unclear. The aim of this study was to analyze the effect of chemotherapy on antitumor immunity in the tumor microenvironment of ovarian cancer. Treatment of ovarian cancer cell lines with various chemotherapeutic agents resulted in upregulated expression of MHC class I and programmed cell death 1 ligand 1 (PD-L1) in a NF-kB-dependent manner and suppression of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
364
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 461 publications
(381 citation statements)
references
References 47 publications
12
364
2
3
Order By: Relevance
“…Conversely, some ICD inducers appear to increase the expression of checkpoint inhibitors and their ligands. The expression of these immunosuppressive molecules, including PD1 and PD-L1, is upregulated on tumor cells or immune cells following radiotherapy, ICD chemotherapy, and type I IFN induction (51,53,65,(71)(72)(73). We found that dinaciclib induced PD-L1 expression on tumor cells in vitro, even after a short exposure to the drug.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Conversely, some ICD inducers appear to increase the expression of checkpoint inhibitors and their ligands. The expression of these immunosuppressive molecules, including PD1 and PD-L1, is upregulated on tumor cells or immune cells following radiotherapy, ICD chemotherapy, and type I IFN induction (51,53,65,(71)(72)(73). We found that dinaciclib induced PD-L1 expression on tumor cells in vitro, even after a short exposure to the drug.…”
Section: Discussionmentioning
confidence: 69%
“…Despite ICD induction, the antitumor activity of dinaciclib as a monotherapy was limited, and only in combination with anti-PD1 Ab did dinaciclib enhance tumor suppression (Figure 1, A-C). Recent studies have shown that the induction of PD1 and PD-L1 expression on tumor and associated immune cells can suppress radiation-or chemotherapy-induced immune responses (50,51), and type I IFN signaling plays an important role in mediating PD1 expression on T cells in tumor (52)(53)(54). Similarly, we found increased expression of PD1 on tumor-infiltrating CD8 + T cells after in vivo dinaciclib treatment ( Figure 6A) and increased expression of PD-L1 on tumor cells after in vitro treatment (Supplemental Figure 8).…”
Section: Dinaciclib Induces Immunogenic Cancer Cell Death and Enhancementioning
confidence: 99%
“…In cases with high IFNg activity and high PD-L1 expression, anti-PD-L1/PD-1 therapy alone is expected to be useful. We have shown that some chemotherapy reagents may induce PD-L1 expression in tumor cells (50). Therefore, during chemotherapy, using these drugs, the inclusion of anti-PD-L1/PD-1 therapy may augment the efficacy of the treatment.…”
Section: Future Directions For Cancer Immunotherapy Based On the Exprmentioning
confidence: 99%
“…Furthermore, recent mouse cancer experiments showed the efficacy of blocking the PD-1/PD-L1 axis following paclitaxel chemotherapy (17). The ability to sample HGSC biopsies at diagnosis and after NACT during surgery gives us an opportunity to ask whether similar responses occur in a clinical setting and if they do, whether this provides a rationale for introducing immunotherapy after NACT rather than in relapsed disease.…”
Section: Introductionmentioning
confidence: 99%